Prosthodontic Rehabilitation of Hereditary Ectodermal Dysplasia in an 11-Year-Old Patient with Flexible Denture: A Case Report - Neha Jain; Dinesh Naitam; Arti Wadkar; Anuradha Nemane; Shiva Katoch; Ashish Dewangan (Hindawi Limited, 2012)
Hereditary ectodermal dysplasia is a rare group of inherited disorders characterized by aplasia or dysplasia of two or more tissues of ectodermal origin such as hair, nails, teeth, and skin. The dental characteristics of this syndrome include anodontia or hypodontia of the primary and/or permanent teeth, hypoplastic conical teeth, and underdevelopment of the alveolar ridges. The options for a definitive treatment plan include fixed, removable or implant-supported prostheses, singly or in combination. This clinical report describes the prosthetic rehabilitation of an 11-year-old boy with hereditary ectodermal dysplasia. Maxillary flexible removable partial denture and mandibular conventional complete denture were fabricated to establish an acceptable masticatory function, speech, and esthetics for the patient.